Desain Prototype Alat Kontrol Serta Deteksi Suhu dan Kelembaban Kandang Ayam Broiler Dengan Metode Fuzzy Berbasis IoT - Abidin, Zainal; Nadhif, Mohammad; Arif, Machnun (ELECTRA : Electrical Engineering Articles, 2022)
In this study, the authors designed the control of temperature and humidity detection in chicken coops using the IoT-based Fuzzy method. Control prototype design and detection of temperature and humidity of broiler cages using IoT-based fuzzy methods, and can be monitored remotely with a smartphone using several components, namely NodeMCU ESP32 as a data processor and controller between the Dht-11 temperature sensor and the output in the form of an LCD to determine the temperature of the cage. directly and also in the form of Smartphone communication data via the internet network with Blynk software. the DHT-11 sensor is in charge of reading the temperature and humidity of the chicken coop, the LCD serves to provide a direct display of the results of the temperature and humidity monitoring data parameters, the blynk application itself is tasked with displaying sensor parameters remotely on a smartphone which in the blynk software can monitor or get notification if the temperature state is crossing a predefined threshold. All components require 24V voltage generated by the 220V SMPS power supply to 24V DC.Â Â The use of fuzzy rules in temperature and humidity control can regulate the output performance of lights and fans that work according to the specified rules.